Integrated analysis of the genomic and transcriptional profile of gliomas with isocitrate dehydrogenase-1 and tumor protein 53 mutations. (5th November 2022) - Liu, Han-Qing; Li, Wei-Xin; An, Ya-Wen; Wu, Tao; Jiang, Guang-Yu; Dong, Yu; Chen, Wei-Xin; Wang, Jian-Chun; Wang, Cheng; Song, Shuo
Background: The gene mutation of isocitrate dehydrogenase-1 (IDH1) is commonly found in LGG and some GBM patients and usually carries tumor protein 53 (TP53) mutations. However, the underlying mechanisms on both mutations of glioma patients in IDH1 and TP53 are still unclear.Aim: To find the potential target markers in GBM and LGG patients with IDH1 and TP53 mutation.Method: A total of 1122 glioma patients from The Cancer Genome Atlas were enrolled and divided as wild-type (without IDH1 and TP53 mutations) or both mutant (both IDH1 and TP53 mutations). The data of clinicopathological characteristics, mRNA, mutations, and copy number alteration were analyzed.Results: IDH1 and TP53 mutations, not gene expression, affect the survival probability of GBM and LGG patients, which might be related to neuron function, immune function, tumor invasion, and metastasis. The effects of the selected gene (EMILIN3, SAA1, VSTM2A, HAMP, IFT80, and CHIC2) on glioma patients could be regulated by IDH1 and TP53 mutations and had a higher survival possibility in these patients.Conclusions: The selected genes in GBM and LGG patients with IDH1 and TP53 mutations could be a potential prognosis marker in the future.